Numerical study on the evaporation rate of an electronic cigarette atomizer - Lei Zhao; Jian Xu; Zhaosheng Yu (Case Studies in Thermal Engineering, 2024)
This work establishes an evaporation model for the electronic cigarette atomizer based on convective mass transfer theory, which is implemented through Fluent user-defined functions (UDFS). By adding the convection–diffusion equation and considering the energy loss caused by evaporation and the temperature variation over the atomizer body, the evaporation rate of the e-liquid from the atomizer is more accurately calculated, compared to the previous evaporation model based on the assumption of constant temperature over the atomizer body. The effects of external airflow velocity, atomizer porosity, heating power, atomizer shape, heating method, and groove width on the average surface temperature and evaporation rate of the atomizer are examined. The results show that compared with other factors, the external air flow velocity has relatively insignificant influence on the evaporation rate of the atomizer. Within a certain range, as the porosity of the atomizer decreases or the heating power increases, the evaporation rate of the atomizer increases. The cylindrical atomizer has better evaporation performance than the cuboid and grooved atomizer, if all atomizer surfaces are heated, however, when the heating area of the grooved atomizer is optimized, i.e., only the surfaces with large evaporation rates are heated, the evaporation rate of a grooved atomizer can be higher than that of a cylindrical atomizer. The evaporation rate increases with increasing groove width, in the parameter range studied.